Linear Types for Large-Scale Systems Verification - Li, Jialin; Lattuada, Andrea; Zhou, Yi; Cameron, Jonathan; Howell, Jon; Parno, Bryan; Hawblitzel, Chris (OOPSLA (in Proceedings of the ACM on Programming Languages), 2022)
Reasoning about memory aliasing and mutation in software verification is a hard problem. This is especially true for systems using SMT-based automated theorem provers. Memory reasoning in SMT verification typically requires a nontrivial amount of manual effort to specify heap invariants, as well as extensive alias reasoning from the SMT solver. In this paper, we present a hybrid approach that combines linear types with SMT-based verification for memory reasoning. We integrate linear types into Dafny, a verification language with an SMT backend, and show that the two approaches complement each other. By separating memory reasoning from verification conditions, linear types reduce the SMT solving time. At the same time, the expressiveness of SMT queries extends the flexibility of the linear type system. In particular, it allows our linear type system to easily and correctly mix linear and nonlinear data in novel ways, encapsulating linear data inside nonlinear data and vice-versa. We formalize the core of our extensions, prove soundness, and provide algorithms for linear type checking. We evaluate our approach by converting the implementation of a verified storage system (about 24K lines of code and proof) written in Dafny, to use our extended Dafny. The resulting system uses linear types for 91% of the code and SMT-based heap reasoning for the remaining 9%. We show that the converted system has 28% fewer lines of proofs and 30% shorter verification time overall. We discuss the development overhead in the original system due to SMT-based heap reasoning and highlight the improved developer experience when using linear types.